Los recursos didácticos y su incidencia en el rendimiento académico de álgebra y funciones de la asignatura de matemáticas en los estudiantes de octavo año de educación general básica y de primer año de bachillerato general unificado de la jornada matutina del colegio de bachillerato “27 de Febrero” de la ciudad de Loja, período académico 2018-2019. Lineamientos alternativos - Martínez Ortega, Michelle Elizabeth (2020)
The constant use of didactic resources within the educational process, at present has become a key tool in order to improve the academic performance that students want to achieve. In this research, the general objective is to determine: how the current use of teaching resources used in algebra and functions by teachers of the mathematics subject influence the academic performance of eighth grade students of Basic General Education and First year of the Unified General Baccalaureate. The research methodology is descriptive and explanatory, for the development of the same, appropriate methods and techniques were used that allowed to give the validity that the research needed and to meet the proposed objectives. The main results of the research are summarized in the following terms: regarding the conceptualization of the term function, most of the students incorrectly resolved the proposed exercise, which concludes that the teaching-learning process used by the teacher is little feasible against the scope of quality academic performance. These results allow us to conclude that the scarce use of teaching resources by the teacher, either due to lack of training or due to lack of inclusion of said resources in the curricular planning, generates a lack of objectivity in the students, thereby affecting the academic performance they want to reach. That is why, based on the results obtained, an alternative guideline was developed on the use of teaching resources, so that students' academic performance can be improved.